2018
DOI: 10.1093/ndt/gfy045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intradialytic cycling exercise on exercise capacity, quality of life, physical function and cardiovascular measures in adult haemodialysis patients: a systematic review and meta-analysis

Abstract: There is insufficient evidence demonstrating whether cycling exercise during HD improves patient outcomes. High-quality, adequately powered RCTs of IDC are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 57 publications
3
81
1
Order By: Relevance
“…Once the full text of those articles was screened, 25 RCTs (1.8% of those identified by the search process) met all inclusion criteria . We also included five systematic reviews for our review of generic HRQOL …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the full text of those articles was screened, 25 RCTs (1.8% of those identified by the search process) met all inclusion criteria . We also included five systematic reviews for our review of generic HRQOL …”
Section: Resultsmentioning
confidence: 99%
“…The authors included two studies which used SF‐36 as a generic HRQOL measure and observed no significant difference in MCS and PCS score between exercise and usual care control groups. However, this meta‐analysis only included two studies with a total sample size of 52 and therefore interpretation is limited due to small sample size …”
Section: Resultsmentioning
confidence: 99%
“…Whilst the above studies suggest exercise may improve LVEF in patients on hemodialysis, our systematic review and meta‐analysis suggested otherwise. An analysis that included only randomized controlled trials of patients undertaking intra‐dialytic cycling found no effect of exercise on LVEF . Again, though, this could be attributed to statistical power.…”
Section: Effects Of Exercise On Cardiovascular Structure and Functionmentioning
confidence: 97%
“…A 2014 systematic review by Sheng et al concluded that it is likely thatintra‐dialytic exercise programs have a positive effect on BP. Interestingly, a recent systematic review and meta‐analysis by our group that looked exclusively at randomized controlled trials of IDC found there is insufficient randomized controlled data to conclusively say whether programs of IDC improve BP control in hemodialysis patients . Safe to say, the data surrounding the effects of exercise on blood pressure are inconclusive.…”
Section: Effects Of Exercise On Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation